Intimate Strangers Commercial Surrogacy in Russia and Ukraine and the Making of Truth - Siegl, Veronika (Cornell University Press, 2023)
Zooming in on commercial surrogacy in Russia and Ukraine, Intimate Strangers addresses market expansion into the intimate spheres of life that play out on women's bodies as mothers and workers. Veronika Siegl follows the inner workings of a surrogacy market marked by secrecy, distrust, and anonymous business relationships. She explores intended mothers' anxious struggles for a child in light of stigmatized infertility and the aggressive biopolitics of motherhood; the uncertain but pragmatic pathways in and out of fertility clinics as surrogates navigate harsh economic realities and resist being objectified or morally judged; and the powerful role of agents and doctors who have found a profitable niche in nurturing and facilitating other people's existential hopes. Intimate Strangers discusses these issues against the backdrop of ultra-conservatism and moral governance in Russia, the rising international popularity of the Ukrainian surrogacy market, and the pervasiveness of neo-liberal ideologies and individualized notions of reproductive freedom.